Population Attributable Risks of Potential Modifiable Factors for Atrial Fibrillation in China: A National Survey - Nie Z; Xu H; Chen C; Gan Y; Chen G; Wang C; Yue W; Yan F; Feng Y; Lu Z (Dove Medical Press, 2022)
Zhiqiang Nie,1,2,* Hongbin Xu,2,* Chen Chen,3,* Yong Gan,2 Guo Chen,1 Chao Wang,2 Wei Yue,4 Feng Yan,5 Yingqing Feng,1 Zuxun Lu2 1Department of Cardiology, Hypertension Research Laboratory, Guangdong Cardiovascular Institute, Guangdong Provincial People's Hospital, Guangdong Academy of Medical Sciences, Guangzhou, 510080, People's Republic of China; 2Department of Social Medicine and Health Management, School of Public Health, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, People's Republic of China; 3Department of Respiratory, Pediatric Intensive Care Unit, Guangzhou Women and Children's Medical Center, Guangzhou Medical University, Guangzhou, People's Republic of China; 4Department of Neurology, Tianjin Huanhu Hospital, Tianjin, People's Republic of China; 5Department of Neurosurgery, Xuanwu Hospital, Capital Medical University, Beijing, People's Republic of China*These authors contributed equally to this workCorrespondence: Zuxun Lu, School of Public Health, Tongji Medical College, No. 13 Hangkong Road, Wuhan, 430030, People's Republic of China, Email zuxunlu@yahoo.com Yingqing Feng, Guangdong Cardiovascular Institute, Guangdong Provincial People's Hospital, Guangdong Academy of Medical Sciences, No. 106 Zhongshan Two Road, Yuexiu District, Guangzhou, 510080, People's Republic of China, Email 651792209@qq.comBackground: There is an association between atrial fibrillation (AF) and overall mortality as well as mobility. It is not known, however, what the preventable burden of AF in China is. This study aims to identify what proportion of the burden of AF may be avoided by modifiable risk factors.Methods: As part of the China National Stroke Screening and Prevention Project, 726,451 adults aged ≥ 40 years were enrolled in a representative cross-sectional study. The following seven factors have been categorized as modifiable risk factors for AF: body mass index, smoking, alcohol consumption, physical inactivity, hypertension, diabetes mellitus, and dyslipidemia. In order to calculate population-attributable risks (PARs), odds ratios (ORs) were calculated for selected risk factors.Results: The crude ORs increased with age (ORs ranged from 1.92 to 4.02). A total of 18,736 cases of prevalent AF have been identified. The overall prevalence of AF was 2.6%. The crude ORs increased with age (ORs range 1.92- 4.03). The adjusted ORs and the corresponding confidence intervals (CIs) for these seven modifiable factors were 1.16 (95% confidence interval [CI]: 1.12- 1.19), 1.56 (95% CI: 1.49- 1.62), 2.15 (95% CI: 2.02- 2.28), 2.07 (95% CI: 2.01- 2.14), 2.71 (95% CI: 2.62- 2.79), 2.10 (95% CI: 2.02- 2.19), 2.52 (95% CI: 2.44- 2.60), and 3.32 (95% CI: 3.18- 3.48), respectively. Accordingly, 59.3% of all cases of AF could be explained by having these modifiable risk factors, among which hypertension accounted for the greatest share.Conclusion: In China, hypertension is the leading preventable cause of AF, and more than half of these cases can be prevented through improving those modifiable risk factors.Keywords: atrial fibrillation, risk factors, population attributable risk, odds ratio, hypertension